Simulación numérica del sloshing - Celis Carbajal y Cols., Miguel A. (2019)
In this paper, we study the effect of sloshing in a compartment of a naval artifact. The sloshing is of great importance in the dynamics of ships and offshore platforms, it is one of the factors that may cause the capsizing. This happens when the ship is under undesirable conditions, such as progressive flooding or fault conditions. The goal is to represent numerically the effect of sloshing. The numerical code is validated through comparisons with numerical and experimental data obtained in the literature. The numerical model is based on the finite difference method, where the Euler equations are solved using the upwind scheme and TVD (Total Variation Diminishing) Roe (1984) and Sweby (1984). The computer code for 2D represents the effect of sloshing in a closed vessel. To adequately represent the reservoir of the naval artifact, we used a structured computational mesh, where the fluid is forced to move by the excitation applied to the tank, this type of excitation is harmonic in sway. For the 3D computer code, a sloped free surface elevation is used as initial condition. Another attempt to realize the versatility of the computer code was the fall of a sphere of water on the free surface of the tank.